Fluorescent Sensing for Nitrated Compounds: Study of the Sensor Microstructure for Improvement on Explosives Detection. (2015) - Rembelski, Damien; Bordet, Jérémy; Brouard, Quentin; Minot, Benoit; Barthet, Christelle; Frénois, Céline
Abstract: In order to response for security purposes, many developments have been developed for counter terrorism and/or military applications. Chemical sensors are promising sensors for trace detection because of their sensitivity and selectivity. Fluorescent sensors have already demonstrated their ability for explosives compounds. In this paper, a polycarbosilane functionalised with pyrene(PCS-Py), a new fluorescent material was tested for explosives detection. Several aspects and characteristic of polymer film were studied: in particular the microstructure of the film and its stability under air flow. Relationship between microstructures and performances were investigated depending of coating methods. Experiments were lead to demonstrate that photo bleaching phenomenon is the main contributing factor in the reduction of stability under air flow.